Inclusive organizational transformation : an African perspective on human niches and diversity of thought - Viljoen, Rica (Transformation and Innovation., 2014)
In Inclusive Organizational Transformation, Dr Rica Viljoen acknowledges that diversity of thought presents both gifts and challenges to leadership in multi-national organizations. Here, Inclusivity is positioned as a radical transformational methodology with the purpose of unleashing the benefits of engagement and diversity of thought. Case studies from Ghana, South Africa, Australia, Peru and Tanzania are included and insights gained from the dynamics observed are shared. A synthesis of Inclusivity is presented in a model, meta-insights are derived and the prerequisites for Inclusivity on in.